Effects of Hypercapnia on Acute Cellular Rejection after Lung Transplantation in Rats. (January 2018) - Tan, Jing; Liu, Yanhong; Jiang, Tao; Wang, Ling; Zhao, Can; Shen, Dongfang; Cui, Xiaoguang
Abstract : Background: Hypercapnia alleviates pulmonary ischemia–reperfusion injury, regulates T lymphocytes, and inhibits immune reaction. This study aimed to evaluate the effect of hypercapnia on acute cellular rejection in a rat lung transplantation model. Methods: Recipient rats in sham-operated (Wistar), isograft (Wistar to Wistar), and allograft (Sprague–Dawley to Wistar) groups were ventilated with 50% oxygen, whereas rats in the hypercapnia (Sprague–Dawley to Wistar) group were administered 50% oxygen and 8% carbon dioxide for 90 min during reperfusion (n = 8). Recipients were euthanized 7 days after transplantation. Results: The hypercapnia group showed a higher oxygenation index (413 ± 78 vs . 223 ± 24), lower wet weight-to-dry weight ratio (4.23 ± 0.54 vs . 7.04 ± 0.80), lower rejection scores (2 ± 1 vs . 4 ± 1), and lower apoptosis index (31 ± 6 vs . 57 ± 4) as compared with the allograft group. The hypercapnia group showed lower CD8 (17 ± 4 vs . 31 ± 3) and CD68 (24 ± 3 vs . 43 ± 2), lower CD8 + T cells (12 ± 2 vs . 35 ± 6), and higher CD4/CD8 ratio (2.2 ± 0.6 vs . 1.1 ± 0.4) compared to the allograft group. Tumor necrosis factor-α (208 ± 40 vs . 292 ± 49), interleukin-2 (30.6 ± 6.7 vs . 52.7 ± 8.3), and interferon-γ (28.1 ± 4.9 vs . 62.7 ± 10.1) levels in the hypercapnia group were lower than those in allograft group. CD4, CD4 + T cells, and interleukin-10 levels were similar between groups. Conclusions: Hypercapnia ameliorated acute cellular rejection in a rat lung transplantation model. Abstract : Randomized exposure to 8% inspired carbon dioxide resulted in preserved lung function, less lung injury, and lower indices of cellular rejection 7 days after lung allograft (different strains) transplantation in a rat model.